2021
DOI: 10.1039/d1nj04526a
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective deprotometalation of alkyl ferrocenecarboxylates using bimetallic bases

Abstract: Our attempts to deprotometalate alkyl ferrocenecarboxylates enantioselectively by using chiral lithium–zinc or lithium–cadmium bases are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 95 publications
0
2
0
Order By: Relevance
“…Complementary synthetic methods (Scheme 13) were based on the metalation of suitable prochiral substrates bearing coordinating groups, such as tertiary amide 43 , 120 amine 36 121 and phosphine oxide 48 , 122 by adducts generated from organolithium compounds and chiral amines, such as (−)-sparteine ( 45 ) and (1 R ,2 R )- N , N , N ′, N ′-tetramethylcyclohexane-1,2-diamine ( 47 ), or, alternatively, by chiral amides. 123…”
Section: Applications Of Ferrocene and Ferrocene Derivativesmentioning
confidence: 99%
“…Complementary synthetic methods (Scheme 13) were based on the metalation of suitable prochiral substrates bearing coordinating groups, such as tertiary amide 43 , 120 amine 36 121 and phosphine oxide 48 , 122 by adducts generated from organolithium compounds and chiral amines, such as (−)-sparteine ( 45 ) and (1 R ,2 R )- N , N , N ′, N ′-tetramethylcyclohexane-1,2-diamine ( 47 ), or, alternatively, by chiral amides. 123…”
Section: Applications Of Ferrocene and Ferrocene Derivativesmentioning
confidence: 99%
“…This was demonstrated by Price and Simpkins who reported the asymmetric deprotolithiation of P,Pdiphenylferrocenephosphine oxide in 54% ee by using lithium bis[(S)-1-phenylethyl]amide [(S)-PEALi] in the presence of trimethylsilyl chloride as an in situ trap. 66 We recently demonstrated that the use of more efficient chiral zinc-based in situ traps could be beneficial for some substrates and managed to reach enantioenriched N,N-dialkylferrocenecarboxamides, 67 O-alkylferrocenecarboxylates 68 and Oisopropylferrocenesulfonate 55 with ee ranging from 64 to 80%. Here, we initially evaluated the use of alkyllithium•chiral diamine chelates to perform the enantioselective deprotolithiation of the substrate 2 before adding a suitable electrophile.…”
Section: Resultsmentioning
confidence: 99%